Main issues in quantity surveying education - Razali, Atikah; Hussien, Suhailah; Tunku Ahmad, Tunku Badariah; Ibrahim, Mohd Burhan (Royal Institution of Surveyors Malaysia, 2024)
This study gives an overview of the literature on Quantity Surveying (QS) Education issues. QS education is the platform for producing highly qualified and skilled Quantity Surveyors for the Malaysian construction sector. As time passes, the quantity of QS graduates generated grows, making companies selective. This phenomenon might contribute to a recent complaint that the performance of QS graduates did not match the employer's expectations, and some prior studies from the QS education provider have started. However, the research assessing the performance of current QS graduates related to their QS education is very limited. Therefore, this research is to investigate issues in QS education that contribute to the quality of QS products. The findings show that there are four main issues in QS education, which are quality, technology, curriculum, and pedagogy used in QS education. The issues discovered will create awareness for the QS education providers in providing the programme that not only meets the employers’ needs but also needs to consider the characteristics of today's students as well as the challenges of educator expertise.